Development of an Integrated Commodity Auction System Based on the English Auction Model for Transaction Transparency and Efficiency - Syopiansyah Jaya Putra; Muhammad Akbar; Siti Saluiatu Rohmah (Jurnal Informasi dan Teknologi, 2025)
Commodity Auction Markets (PLK) serve as a platform for interactions between sellers and buyers to conduct transactions through a price-bidding system. Traditionally, these auctions are held offline to facilitate transactions between farmers, farmer groups, traders, businesses, and other commodity buyers. However, conventional auctions face multiple challenges, including inefficiencies in execution time, limited access to information for buyers, and high operational costs. This study aims to design and develop an Integrated e-Auction Market System (PLT) based on the English Auction model. The system supports the entire auction process from preparation, announcement, and bidding, to winner determination and transaction finalization. System development was conducted using the Rapid Application Development (RAD) approach for planning, analysis, design, and implementation phases. Unified Modeling Language (UML) tools were utilized to model system design components.The web-based PLT system successfully integrates all auction processes efficiently and transparently. It provides stakeholders with access to commodity catalogs, session schedules, and detailed transaction information, while enabling real-time online auctions. The implementation of this system is expected to broaden commodity marketing networks, increase local government revenues, and significantly reduce auction operational costs particularly venue rental expenses.